Preparation of Edible Film from A Mixture of Carrot Extract (Daucus carota L.) with Tapioca Flour, Wheat Flour, and Glycerine - Zaidar, Emma (Talenta Publisher, 2021)
The preparation of edible film from carrot extracts (Daucus Carota, L) with the addition of tapioca flour, wheat flour, and glycerin was carried out. The edible film was prepared by mixing carrot extract, tapioca flour, and wheat flour, and then heated and added with glycerin and stirred up. The homogeneous solution was put into an acrylic plate to form an edible film and dried in an oven at 40oC for Â± 2 days. The edible film formed was characterized and analyzed its nutrition content. The tensile strength and elasticity of edible film with a ratio of 5 g tapioca flour and 5 g wheat flour were 0.1028 KgF/mm2 and 39.83% respectively. The thickness of edible film with a ratio of 2.5 g of tapioca flour and 7.5 g of wheat flour 7.5 g was 0.26 mm. The better nutrition content was found on edible film with a ratio of 5 g tapioca flour and 5 g wheat flour which has 13.94% moisture content, 2.67% ash content, 4.93% protein content, and 2.90% fat, 75.56% carbohydrate content, and 410.34 ppm carotene content. Organoleptic test edible film of color, taste, texture, and aroma gave an average score of 3 (like), because of the shiny color, crunchy taste, smooth texture, and interesting edible film. Based on the test indicated that people accepted the edible film produced.